Fernando Ocáriz, Amar con Obras: a Dios y a los hombres. Madrid, Palabra, 2015 - Chang Chuyes, Guillermo (Mercurio Peruano. Revista de Humanidades, 2020)
Fernando Ocáriz, Amar con Obras: a Dios y a los hombres. Madrid, Palabra, 2015.
Keywords: Reseña